Estimation of calcium and magnesium in serum and urine by atomic absorption spectrophotometry - Thin, Christian G. (1967)
A method has been described for the estimation of calcium and magnesium in serum and urine using atomic absorption spectrophotometry. The precision and accuracy of the techniques have been determined and were found to be acceptable. The range of values for calcium and magnesium in the sera of normal adults was found to be: serum calcium (corrected to a specific gravity of 1·026) 8·38-10·08 mg. per 100 ml.; serum magnesium 1·83-2·43 mg. per 100 ml.